A new species of the genus Hemiphyllodactylus Bleeker, 1860 (Squamata: Gekkonidae) from Goa, India - Khandekar, Akshay; Parmar, Dikansh S.; Sawant, Nitin; Agarwal, Ishan (Zootaxa, 2021)
We describe a distinct new species of the genus Hemiphyllodactylus based on three specimens collected from semi-urban areas in Goa state of India. The new species can be easily distinguished from all peninsular Indian congeners by its small body size (SVL up to 32.4 mm), having 16–18 dorsal scales and 13 or 14 ventral scales at mid-body contained within one longitudinal eye diameter, nine or ten precloacal pores separated by 1–5 poreless scales from a series of 10–12 femoral pores on each thigh in males, lamellar formula of manus 2222 and of pes 2323 & 2333, as well as subtle colour pattern differences. Mitochondrial sequence divergence confirms the distinctiveness of the new species, which is not closely allied to either the South Indian or Eastern Ghats clades of Indian Hemiphyllodactylus and appears to be a member of a third Indian Hemiphyllodactylus clade. Hemiphyllodactylus goaensis sp. nov. is the first member of the genus to be described from the northern Western Ghats region as well as Goa state, and also only the second Indian Hemiphyllodactylus known from < 100 m asl. Hemiphyllodactylus goaensis sp. nov. extends the known distribution of the genus in western India 560 km north in aerial distance and highlights that the genus is more widely distributed than previously thought and most likely contains numerous undescribed species. We also provide final museum numbers for type specimens of H. arakuensis and the holotype of H. kolliensis.